DESIGN INOVASI MEDIA FLASHCARD MAHASISWA PG PAUD UMSURABAYA UNTUK MENANAMKAN KONSEP MEMBILANG ANGKA 1 – 9 PADA ANAK USIA DINI - wahono wahono (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
This  study  aims  to  inspire  teachers  (PAUD)  and  to  gain  an  overview  of  the  use flashcard  media  In  Enhancing  The  Ability  To  Instill  The  Concept  Of  Counting  Numbers  1‐9 In  Early  Childhood.  Research  was  conducted  on  students  The  study  program  Teacher Education  Early  Childhood  Education,  University  of  Muhammadiyah  Surabaya.  Experience teaches  counting  the  most  widely  experienced  by  children  aged  five  and  six  years. 90%  of the  observation  of  early  childhood  teachers  teach  the  concept  of  counting  the  numbers  1‐9  are  correct.  To  strengthen  the  child's  responses,  teacher  invites  children  to  count  the number  of  fingers  together  left  hand  and  right  hand.  After  the  children  were  asked  to  try yourself counting the fingers of their left and right hands. From  interviews  with  teachers  and  parents  85%,  the  They've  been  able  to  train children  to  count  the  objects  that  exist  around  children  whether  at  home,  on  the  road,  as well  as  schools.  From  the  observations  gathered  researchers  found  75%  of  teachers  and parents have not been used to teach counting while bernyannyi, children are introduced to the  concept  of  numbers,  for  example  through  the  songs  that  match  the  numbers  that  will be introduced, for example: the song I love mom.  Keywords:  flashcard media, count the numbers 1‐9